HOW THE NEW UZBEKISTAN CONSTITUTION ENSURES A FREE AND PROSPEROUS LIFE (Yangi O'zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2024)
Constitutional reforms often seem distant from our daily lives, but the new constitution of Uzbekistan marks a turning point that directly impacts every citizen. As we embrace the concept of "yangi o'zbekiston" (New Uzbekistan), we're witnessing a fundamental transformation in how our nation protects and empowers its people.